2022
DOI: 10.3390/ijms232314909
|View full text |Cite
|
Sign up to set email alerts
|

Methyl P-Coumarate Ameliorates the Inflammatory Response in Activated-Airway Epithelial Cells and Mice with Allergic Asthma

Abstract: Methyl p-coumarate (methyl p-hydroxycinnamate) (MH) is a natural compound found in a variety of plants. In the present study, we evaluated the ameliorative effects of MH on airway inflammation in an experimental model of allergic asthma (AA). In this in vitro study, MH was found to exert anti-inflammatory activity on PMA-stimulated A549 airway epithelial cells by suppressing the secretion of IL-6, IL-8, MCP-1, and ICAM-1. In addition, MH exerted an inhibitory effect not only on NF-κB (p-NF-κB and p-IκB) and AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Recent studies have revealed that the combination of airway epithelial cells and eosinophils is weakened by the suppression of airway epithelial cell-derived cytokines such as IL-6 and MCP-1 [ 15 ]. Compounds that can suppress airway epithelial cell-derived cytokines and airway cell-eosinophil adhesion exert ameliorative effects against bronchial inflammation in experimental models of AA [ 16 , 35 , 36 ]. In our in vitro study, ARO inhibited not only IL-1β, IL-6, TNF-α, and MCP-1 production in A549 cells but also airway cell-eosinophil cohesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed that the combination of airway epithelial cells and eosinophils is weakened by the suppression of airway epithelial cell-derived cytokines such as IL-6 and MCP-1 [ 15 ]. Compounds that can suppress airway epithelial cell-derived cytokines and airway cell-eosinophil adhesion exert ameliorative effects against bronchial inflammation in experimental models of AA [ 16 , 35 , 36 ]. In our in vitro study, ARO inhibited not only IL-1β, IL-6, TNF-α, and MCP-1 production in A549 cells but also airway cell-eosinophil cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…To detect immune cells and Th2 cytokines in the BALF, mice were anesthetized as per previously reported conditions (intraperitoneal injection of Zoletil and xylazine) [ 16 ]. Immune cell morphology was distinguished using Diff-Quik staining, and the number of cells was determined using a light microscope (400× magnification) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] The previous study has demonstrated that intraperitoneal injection of OVA and alum once a week for 2 weeks is the most straightforward and effective approach to induce an asthmatic reaction in mice. 11 However, the inconsistent use of sensitizing OVA doses in current studies [12][13][14] and the lack of research on their effect on AHR necessitate further investigation. Therefore, we conducted a study using increasing doses (0, 10, 20, 50, and 100 μg) of sensitizing OVA in a BALB/c murine model of asthma to evaluate their impact on AHR to methacholine (MCh), as well as histological changes, eosinophilic infiltration, and epithelial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl p-coumarate, an esterified derivative of p-coumaric acid and a naturally occurring compound in plants, has been shown to be an effective agent for reducing inflammation in an experimental in vivo model of allergic asthma, reducing the influx of immune cells and mucus secretion in the lung, among other activities [9].…”
mentioning
confidence: 99%